Analysis of the stress-strain state of plates under impact loading - Астанін, В.В.; Бородачов, М.М.; Богдан, С.Ю. (Proceedings of National Aviation University (archive), 2007)
The problem concerning the stress-strain state of a plate under load impact with various intensity levels of collision momentum applying finite-element method was considered.